Good Manufacturing Practices in Black Tea Processing at PT. XYZ - Ervina Mela; Dian Dwi Novianti (Indonesian Journal of Food Technology, 2023)
Black tea comes from perfectly fermented tea leaves and is one of Indonesia's main export commodities. The high level of black tea exports requires producers to produce high-quality products. One way to realize quality and safe products is by implementing Good Manufacturing Practices (GMP). The purpose of this study was to determine the application of Good Manufacturing Practices (GMP) in black tea processing at PT XYZ. The research method was carried out by collecting primary and secondary data. Primary data were obtained through direct observation and practice in the field, as well as interviews with related parties. While secondary data is obtained through records and archives such as libraries and references to other supporting sources, The variables observed were company location, buildings, sanitation facilities, production equipment, raw and supporting materials, production processes, personnel hygiene, waste handling, production support facilities, and product packaging. The results showed that PT XYZ as a whole had implemented GMP well in the black tea processing industry, with GMP implementation levels ranging from 75–100%. The building GMP component has an implementation rate of 80%, with the "walls and floors" sub-component not properly implemented. In addition, the personnel hygiene component has an implementation rate of 75% with the sub-component "hygiene monitoring for personnel who have direct contact with the product," which is still not properly implemented.